WOMEN, BORDERS AND RESISTANCE IN IBTISAM BARAKAT’S BALCONY ON THE MOON: COMING OF AGE IN PALESTINE - Balachandran, Indu; Somaraj, Anej (ShodhKosh: Journal of Visual and Performing Arts, 2023)
Palestine territories, characterized by constant conflicts and associated violence, are known for the various borders governing the lives of their inhabitants. Apart from borders with geopolitical significance, there are also other kinds of borders operating on the basis of gender, religion and ethnicity. For women in Palestine, borders abound in multiple forms, and resistance includes dealing with the restrictions imposed by political borders and those imposed by gender. Though narratives dealing with geopolitical conflicts in Palestine have come up, not much scholarly attention has been paid to the negotiation of borders, nationalism and territorialization of memory as experienced by women. Stories and experiences narrated by women from the margins throw a new light upon the multiple effects of settler colonialism in Palestine. Ibtisam Barakat’s memoir Balcony on the Moon: Coming of Age in Palestine is one such work focusing on the author’s growing up years in Palestine and women’s ways of managing the precariousness and control mechanisms operating around them. It also throws light upon their domestic existence in the midst of political conflicts. This paper aims to explore the lived experiences of women in Palestine borderlands and their bond with their homeland as portrayed in Ibtisam Barakat’s memoir. It also intends to study how the memories of negotiating gender and border are used as a means of resistance against both patriarchy and settler colonialism.